Frontobasal Fractures - Litschel, Ralph; Kühnel, Thomas S.; Weber, Rainer (Facial Plastic Surgery, 2015)
Frontobasal fractures occur in up to 24% of head injuries and often require a multidisciplinary approach. Besides the common bone fractures, the complex anatomy can cause damage to the sense of vision and smell. Further possibly lethal complications such as cerebrospinal fluid leak followed by meningitis or internal carotid bleeding can follow. Diagnostic and treatment options are reviewed with a focus on the endoscopic endonasal approach.
Keywords: frontobasal trauma; frontal sinus trauma; carotid trauma; cerebrospinal fluid leak; dural lesion; traumatic optic neuropathy; endoscopic endonasal